How do teachers’ roles transform in metaverse classroom? The mechanisms of awe experience and differences across teaching stages - Li, Hanxi; Liu, Yuanxiong; Du, Jiang; Pan, Younghwan (Frontiers in Psychology, 2026)
With the rapid development of metaverse technologies in education, how teachers adapt to this emerging environment has become a critical issue. This study explores teachers’ emotional experiences and adaptation mechanisms within metaverse classroom. Grounded in awe experience theory and role theory, it examines how classroom features influence teachers’ role adaptation through both positive and negative awe experiences, thereby affecting teaching satisfaction and engagement. Using survey data from 692 primary and secondary teachers, Partial Least Squares Structural Equation Modeling (PLS-SEM) and Multi-Group Analysis (MGA) were conducted. Results show that the immersive, interactive, technically complex, and decentralized metaverse environments significantly enhance positive awe while unexpectedly reducing negative awe. These emotional responses improve teachers’ role clarity, leading to higher teaching satisfaction and engagement. Moreover, Multi-group analysis reveals stage-based differences: primary school teachers are more easily inspired by positive awe, whereas high school teachers demonstrate stronger technological adaptability and emotional regulation. This study not only expands the understanding of emotional mechanisms among teachers in educational technology research but also provides stage-specific and differentiated practical implications for teacher training and instructional design.